Tranexamic Acid Improves Memory and Learning Abilities in Aging Mice - Hiramoto K; Yamate Y; Matsuda K; Sugiyama D; Iizuka Y (Dove Medical Press, 2020)
Keiichi Hiramoto,1 Yurika Yamate,1 Kazunari Matsuda,2 Daijiro Sugiyama,2 Yasutaka Iizuka2 1Department of Pharmaceutical Sciences, Suzuka University of Medical Science, Suzuka, Mie 513-8670, Japan; 2R&D Department, Daiichi Sankyo Healthcare Co., LTD, Shinagawa-ku, Tokyo 103-8234, JapanCorrespondence: Keiichi Hiramoto Department of Pharmaceutical SciencesSuzuka University of Medical Science, 3500-3 Minamitamagakicho, Suzuka, Mie 513-8670, JapanTel +81-59-340-0575Fax +81-59-368-1271Email hiramoto@suzuka-u.ac.jpPurpose: Although the onset mechanism of Alzheimer’s disease, which co-occurs with aging, has been extensively studied, no effective methods that improve the decline in memory and learning abilities following aging have been developed. Tranexamic acid provided promising results for ameliorating photo-aging and extending the natural lifespan. However, it is unknown whether it affects the decline in memory and learning abilities due to aging. In this study, we examined the effect of tranexamic acid on memory and learning abilities of naturally aging mice.Methods: ICR mice were orally administered with tranexamic acid (12 mg/kg/day) three times weekly for 2 years, and their memory and learning abilities were compared between the tranexamic acid-treated and non-treated groups.Results: The decline in memory and learning abilities due to aging was ameliorated by tranexamic acid administration. The expression of plasmin and amyloid-β decreased following the treatment with tranexamic acid. Furthermore, the number of M1-type brain macrophages diminished and that of M2 macrophages increased. In addition, administration of tranexamic acid decreased the concentrations of interleukin (IL)-1β and tumor necrosis factor-α, while it increased the levels of IL-10 and transforming growth factor-α in the brain.Conclusion: These results indicated that tranexamic acid suppressed the secretion of the inflammatory cytokines aging M1-type macrophages, thereby improving age-related memory and learning abilities.Keywords: plasmin, chronic inflammation, M1-type macrophage, M2-type macrophage, TNF-α, IL-1β